APPLICATION OF ACTIVE BRACING SYSTEM ON HOSPITAL BUILDING IN DEPOK UNDER EARTHQUAKE EXCITATION - Hakiki, Irvan
Hospital is one of the important facilities that must be designed better than other civil structures. Excessive deformation that occurs in the hospital due to earthquake loads can cause discomfort or danger for the users of the building. Therefore, excessive deformation must be controlled by applying an active control system at the hospital. This paper discusses the application of active control systems on the hospital in Depok using active bracing system. Active bracing system provides control force on the hospital as a mechanism of energy dissipation due to earthquake loads. Structure was tested with three seismic loads: El Centro 1940 earthquake, Kobe 1995 earthquake, and Chichi 1999 earthquake. Seismic loads was adapted to the construction site of the hospital (Depok, region 3). Configurations of stiffeners selected based on the smallest response of the hospital. Stiffeners were designed by the maximum control force and nominal force in resisting local buckling of stiffeners. Analyses were performed by assessing the effectiveness of bracing systems active at the hospital excited earthquake loads.